Exogenous selenium enhances cadmium stress tolerance by improving physiological characteristics of Artemisia argyi seedlings - Yaxin Yu; Yingbin Yang; Yu Guo; Meiqi Pan; Wenfang Hao (Scientific Reports)
Abstract The contamination of Chinese medicinal materials with cadmium (Cd) is a pressing global issue that poses significant risks to human health. The beneficial effects of selenium (Se) have been established in improving plant growth and reducing Cd accumulation in plant under Cd stress. This study employed soil cultivation experiments to investigate the remediation effects of exogenous Se (0, 0.5, 1, and 2 mg kg⁻1) under varying levels of Cd stress (0, 0.6 and 4 mg kg⁻1). The findings revealed that Cd stress markedly impaired seedling growth, biomass, and physiological characteristics in Artemisia argyi. Regardless of Cd levels, exogenous Se significantly enhanced seedling biomass, improved antioxidant enzyme activity, and increased the plant’s antioxidant capacity, thereby mitigating Cd stress. Additionally, exogenous Se promoted A. argyi plant growth, decreased malondialdehyde (MDA) content in the shoots, and under two Cd stress environments of 0.6 and 4 mg kg⁻1, the application of 1 mg kg⁻1 Se reduced the Cd content in the aboveground parts of seedlings by 31.99 and 82.21%, respectively. We conclude 1 mg kg⁻1 Se could represent a promising strategy to contribute to the development and sustainability of crop production on soils contaminated with Cd at a concentration of up to 0.6 and 4 mg kg⁻1. These results indicate that exogenous Se activates physiological and biochemical defense mechanisms in A. argyi seedlings against Cd stress, offering a foundation for cultivating high-yield, high-quality A. argyi in Cd-contaminated soils.